2004
DOI: 10.1002/lapl.200310044
|View full text |Cite
|
Sign up to set email alerts
|

Laser even harmonics generation by a plasma embedded in a static electric field

Abstract: Even order harmonics generation of the laser radiation due to electron-ion collisions in a plasma embedded in a constant electric field is investigated theoretically. Even harmonics are generated because the presence of a static electric field removes the invariance of the electron distribution function under the symmetry operation of velocity direction inversion. Efficiency generation dependencies are investigated vs different significant parameters as: harmonics number; the ratio of the electron quiver velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…This property of the even harmonics has been previously noted in a theoretical study of laser even harmonics generation by a plasma embedded in a static electric field [10].…”
Section: Resultsmentioning
confidence: 78%
“…This property of the even harmonics has been previously noted in a theoretical study of laser even harmonics generation by a plasma embedded in a static electric field [10].…”
Section: Resultsmentioning
confidence: 78%
“…For V E greater than V T (t) by a factor larger than 4 the same initial EDF first becomes elongated in the perpendicular direction to that of the laser polarization, and afterwards evolves as in the case V E /V T (t) > 2÷4. In both cases, far from the critical transition values of V E /V T (t), the field modified EDF may profitably be approximated by an EDF with a maxwellian shape and two different temperatures, perpendicular and parallel to the laser electric field (anisotropic bi-maxwellian EDF) [15][16][17][18]. 4).…”
Section: Account Of the Plasma Influencementioning
confidence: 99%
“…The generation of second harmonic radiation by the propagation of linearly polarized laser beams in magnetized plasma has been reported [13]. Ferrante et al [14] have theoretically shown the generation of even harmonics of a laser propagating in plasma embedded in a static electric field. In addition, Jha et al have recently reported harmonic generation by oblique incidence of linearly, as well as circularly, polarized laser beams in plasma [15,16].…”
Section: Introductionmentioning
confidence: 99%